Superoxide dismutase and myeloperoxidase activities in polymorphonuclear leukocytes in acne vulgaris - Kurutas, E.B. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2005)
Background and design: Acne vulgaris frequently occurs in the second decade oflife. The pathogenesis of the disease is multifactorial and in the present study, we aimed to investigate the role of reactive oxygen species in the inflammation of acne by determining the activities of myeloperoxidase (MPO) and superoxide dismutase (SOD) in polymorphonuclear leukocytes (PMN). Materials and methods: Forty-three patients with acne vulgaris and 24 healthy controls were enrolled. The severity of the acne was categorized from mild (subjects with only comedonic lesions) to severe (subjects with nodulocystic lesions). SOD and MPO activities in PMN were measured spectrophotometrically. Results: There was no significant difference in the activity of MPO between the patients and controls. However, SOD activity in PMN was significantly lower in the patients than in the controls (p<0.001). No correlation was detected between the activities of enzymes and the severity of the disease. Conclusion: Propionibacterium acnes may not play a primary role in the pathogenesis of acne as a bacterium. However, the low activity of SOD in PMN may be responsible for the increased levels of superoxide anion radicals in the epidermis. New anti-acne drugs should include substances with lymphocyte stimulating and anti-oxidative properties.
Keywords: Acne Vulgaris; Akna navadna; akne; Chemistry; dermatologija; Neutrophils; Nevtrofilci; Peroksidaza; Peroxidase; Spectrophotometry; Spektrofotometrija; Superoksidna dismutaza; Superoxide Dismutase